2016
DOI: 10.5194/hess-20-3843-2016
|View full text |Cite
|
Sign up to set email alerts
|

Local impact analysis of climate change on precipitation extremes: are high-resolution climate models needed for realistic simulations?

Abstract: Abstract. This study explores whether climate models with higher spatial resolutions provide higher accuracy for precipitation simulations and/or different climate change signals. The outputs from two convection-permitting climate models (ALARO and CCLM) with a spatial resolution of 3-4 km are compared with those from the coarse-scale driving models or reanalysis data for simulating/projecting daily and sub-daily precipitation quantiles. Validation of historical design precipitation statistics derived from int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 55 publications
2
45
1
Order By: Relevance
“…Although the importance of the model spatial resolution for the simulation of summer extreme precipitation has also been emphasized in previous studies (Tabari et al 2016, Karmacharya et al 2017, Gadian et al 2018, Tabari and Willems 2018, a clear pattern is not found in this study. Nevertheless, SDS is mostly less than one except for winter in north and west Europe (figures 6 and S12(b)-(e)).…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…Although the importance of the model spatial resolution for the simulation of summer extreme precipitation has also been emphasized in previous studies (Tabari et al 2016, Karmacharya et al 2017, Gadian et al 2018, Tabari and Willems 2018, a clear pattern is not found in this study. Nevertheless, SDS is mostly less than one except for winter in north and west Europe (figures 6 and S12(b)-(e)).…”
Section: Resultscontrasting
confidence: 56%
“…The projections are usually performed by means of global climate models (GCMs). GCM simulations are, however, typically at course spatial (hundreds of kilometers) and temporal (daily) resolutions which poses some limitations to accurately capture more details such as land topography or orographic effects and mesoscale processes (Tabari et al 2016). Therefore, dynamical downscaling has been implemented using regional climate models (RCMs), which provide an improved representation of the physical processes in the atmosphere and the topographic variability which cannot be captured by the coarse resolution of GCMs (Dosio andFischer 2018, Soares andCardoso 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying assumption of stationarity is generally not expected to be valid at subhourly to subdaily precipitation durations under projected 21st century warming (Cheng & AghaKouchak, ; Lenderink & Van Meijgaard, ), but the reliability of stationarity assumptions in multiday duration prediction is less clear (Nissen & Ulbrich, ). Alternatives that develop IDF information from global or regional climate models may not be practical for mountain areas given the difficulties of downscaling precipitation in complex terrain (Tabari et al, ). Together these challenges call for simultaneous efforts to test and improve standard IDF techniques in snow‐dominated mountains, as done in this study, combined with improved atmospheric and snowpack energy budget modeling efforts that better consider the effects of changing climate on extreme snowmelt and precipitation processes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our work provides a theoretically consistent methodology that can be applied to disaggregate actual rainfall (or model outputs) at fine time scales, which can be used in several fields that have been significant catalysts for the development of recent hydrological research. In fact, a wide range of studies concerning, e.g., climate-related issues, resilience of urban areas to hydrological extremes, and online prediction/warning systems for urban hydrology require accurate characterization of rainfall inputs at fine time scales Lombardo et al, 2009;Fletcher et al, 2013;Tabari et al, 2016;McCabe et al, 2017]. Hence, complete rainfall disaggregation methods with solid theoretical basis together with reliable data series are crucial to meet these needs.…”
Section: 1002/2017wr020529mentioning
confidence: 99%